The inventory of edible mushroom in Kamojang Nature Reserve and Nature Park, West Java, Indonesia - PUTUT FAJAR ARKO; BETTY MAYAWATIE MARZUKI; JOKO KUSMORO (Biodiversitas Journal of Biological Diversity, 2017)
Arko PF, Marzuki BM, Kusmoro J. 2017. The inventory of edible mushroom in Kamojang Nature Reserve and Nature Park, West Java, Indonesia. Biodiversitas 18: 530-540. Research on the potential of macroscopic fungi in the forests of Indonesia as food and medicine still hasn't much been done. Until now, the biodiversity data of macroscopic fungi are destitute. On the other hand, we are faced with the rapid rate of decline of biodiversity both by natural processes and by human activities. The purpose of this study was to determine the species of edible mushroom in Kamojang Natural Reserves and Nature Park, Bandung-Garut Districts, West Java. The method used in this research were exploration method assisted with line transect and semi-structural interviews to people around Kamojang Nature Reserves and Nature Parks. The results of the study were obtained and analyzed descriptively. Thirty-five species of macroscopic fungi that categorized as edible mushroom were found in Kamojang Nature Reserves and Nature Parks, i.e. Armillaria sp., Auricularia sp., two species of Cerrena, Clavulina sp., Fistulina hepatica, two species of Ganoderma, Inocybe sp., four species of Marasmiellus, four species of Marasmius, Microporus xanthopus, Oudemansiella sp., Phellinus sp., Phlebia sp., Pleurotus sp., Pluteus thomsonii, Polyporus meridionalis, Polyporus tenuiculus, Polyporus udus, Postia sp., Schizophyllum commune, Stereum rameale, Stereum gausapatum, Stereum ostrea, Suillus sp., Xylaria longipes, and two species of Xylaria. From the 35 species of edible mushroom, only ten species that had been used by villagers in Kamojang as food and medicine, i.e. Armillaria sp., Auricularia sp., Fistulina hepatica, both species of Ganoderma, Marasmiellus sp.2, Oudemansiella sp., Polyporus meridionalis, Polyporus tenuiculus, and Polyporus udus.